Effects of Combination of Cisplatin and Paclitaxel Chemotherapy on Tumor Mass in Nasopharyngeal Carcinoma Patients at Dr. Wahidin Sudirohusodo Hospital Makassar with the RECIST Method: Efek Kombinasi Kemoterapi Cisplatin dan Paclitaxel Terhadap Massa Tumor pada Pasien Karsinoma Nasofaring di RSUP Dr. Wahidin Sudirohusodo Makassar dengan Metode RECIST - Hakim, Azima; Wahyudin, Elly; Pieter, Nova Audrey Luetta (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2023)
Background: Nasopharyngeal Carcinoma (NPC) is a malignant tumor that grows from epithelial cells that line the surface of the nasopharynx and has a tumor position close to the base of the skull, vital structures, and anatomical locations that are difficult to reach and various symptoms are the cause of increased patient mortality and morbidity rates. This research aims to identify the most effective chemotherapy effect on reducing tumor mass in nasopharyngeal cancer patients. Material and Methods: This study was conducted retrospectively based on patient medical record data from January 2019 to December 2021 at Dr. Wahidin Sudirohusodo General Hospital. Inclusion criteria included NPC patients who received cisplatin, carboplatin, paclitaxel, and docetaxel chemotherapy and had complete data on tumor mass size before and after receiving chemotherapy from Series I to Series VI. The resulting assessment of tumor mass size was further categorized using RECIST. Results: A total of 166 NPC patients met the inclusion criteria. The results of the study obtained that NPC patients suffered more in men than women, most NPC patients were aged (41-50), Stage IVA had the highest percentage found in NPC patients, Histopathology based on WHO type III was most commonly found in 109 patients, 70 patients used the Cisplatin+Paclitaxel chemotherapy regimen, 55 patients used the Cisplatin+Paclitaxel chemotherapy regimen had a partial tumor mass response. Conclusions: The combination of Cisplatin + Paclitaxel has the most partial response to the tumor mass of NPC patients at Wahidin Sudirohusodo General Hospital, Makassar.